Procrastination - Klingsieck, Katrin B.; Steel, Piers (International Encyclopedia of Social & Behavioral Science)

CFD-Untersuchung der Fluiddynamik und des Wärmeübergangs bei einphasiger Strömung im welligen Spalt zwischen Thermoblechen - Piper, Mark; Tran, Julian M.; Kenig, Eugeny Y. (Chemie Ingenieur Technik)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Masked priming of complex movements: perceptual and motor processes in unconscious action perception - Güldenpenning, Iris; Braun, Jelena F; Machlitt, Daniel; Schack, Thomas (Psychological Research)

Neurophysiologische Korrelate der Verarbeitung der Blickrichtung im Basketball bei der Passbeurteilung - Koester, Dirk; Schütz, Christoph; Güldenpenning, Iris; Schack, Thomas (The Athlete’s Brain: Neuronale Aspekte motorischer Kontrolle im Sport. 14. Jahrestagung der dvs-Sektion Sportmotorik)

Minimum participation rules in international environmental agreements: empirical evidence from a survey among delegates in international climate negotiations - Kesternich, Martin (Applied Economics)
Keywords: Economics and Econometrics

Extreme weather experiences and climate change beliefs in China: An econometric analysis - Dai, Jing; Kesternich, Martin; Löschel, Andreas; Ziegler, Andreas (Ecological Economics)
Keywords: Economics and Econometrics; General Environmental Science

Entwurf und Anwendung einer erweiterten Zustandsüberwachung zur Verlässlichkeitssteigerung selbstoptimierender Systeme - Sondermann-Woelke, Christoph
Das Wirkparadigma der Selbstoptimierung ermöglicht mechatronischen Systemen sich autonom und flexibel an veränderte Betriebssituationen anpassen zu können. Um selbstoptimierende Systeme verlässlich zu gestalten und darüber hinaus Selbstoptimierung zur Verlässlichkeitssteigerung des Systems zu nutzen, werden in dieser Arbeit der Entwurf und die Anwendung einer erweiterten Zustandsüberwachung dargestellt. Darin wird eine klassische Zustandsüberwachung mit dem Wirkparadigma der Selbstoptimierung verbunden. Für den Entwurf der erweiterten Zustandsüberwachung wird aufgezeigt, welche Schritte erforderlich sind, damit das Wirkparadigma der Selbstoptimierung genutzt und gleichzeitig das selbstoptimierende System abgesichert werden kann. Die Basis für den Entwurf der erweiterten Zustandsüberwachung stellt die Spezifikation der Prinziplösung selbstoptimierender Systeme dar. So können das System und die erweiterte Zustandsüberwachung in den frühen Phasen des Entwicklungsprozesses konsistent entworfen werden. Hinsichtlich der Anwendung werden drei Aspekte betrachtet. Erstens werden die Entwurfsschritte anhand des Anwendungsbeispiels umgesetzt und bewertet. Zweitens werden die unterschiedlichen Betriebsstrategien auf einem realen Demonstrator implementiert und erprobt, um vor allem das Konzept des Umschaltens auf verlässlichkeitsorientierte Ziele im Fehlerfall zu bewerten. Drittens werden Simulationen durchgeführt, die über die Möglichkeiten des realen Demonstrators hinausgehen. Die exemplarische Anwendung zeigt, dass die erweiterte Zustandsüberwachung eine Steigerung der Verlässlichkeit im Betrieb mittels Selbstoptimierung ermöglicht.
Keywords: Verl{\

,,…, als habe dort niemals eine Insel gestanden.“ Wolfgang Hildesheimers und Hans Werner Henzes Das Ende einer Welt als Erzählung und Rundfunkoper - Eickmeyer, Jost; Tumat, Antje (Literatur für Leser)
An den Schluss seiner ersten unter dem programmatisch-spöttischen Titel Lieblose Legenden veröffentlichten Prosa-Sammlung setzt Wolfgang Hildesheimer effektvoll Das Ende einer Welt. Dem eschatologischen Beiklang der Rede vom Ende wird schon im Titel lakonisch Paroli geboten: Es handelt sich nur um das Ende ,,einer“ Welt, jedoch einer, die in aller hyperbolischen Absurdität mit europäischer Kunst und Kultur assoziiert werden kann, deren gewaltsamer Untergang in Diktatur und Krieg den Lesern sowohl 1952 als auch nach der letzten revidierten Publikation 1962 noch deutlich vor Augen gestanden haben dürfte. Das ,,Echte und Bleibende“, das die Marchesa di Montetristo (eine schon namentlich gekennzeichnete melancholische Version von Alexandre Dumas’ rachedurstigem Grafen) auf ihrer künstlichen Insel südöstlich von Murano pflegt, lässt sich als Sammelsurium alteuropäischer Kulturbeflissenheit lesen: an Personen ein Abraham-a-Santa-Clara-Forscher und ein Neo-Mystiker gleichen Namens, eine polnische Tänzerin, die als ,,Doppelbegabung“ (EW, 9) zugleich den Jugendstil erneuert, eine italienische Astrologin, die Kulturgeschichte betreibt, ein womöglich deutsch-italienischer monarchistischer Politiker, ein Schweizerischer Musikforscher (und -fälscher), ein französischer Flötenvirtuose und Nachfahre Jean-Pierre Bérangers, eine vermutlich irische Anhängerin keltischer Folklore. Der Palazzo der Marchesa gleicht äußerlich jenem venezianischen Gebäude, in dem Richard Wagner starb, in seinem Inneren sind gar ,,alle Stilepochen von der Gotik an vertreten“ (EW, 9), ein Cembalo gehörte einst Jean-Philippe Rameau, auch die konzertierende Flöte scheint von historischem Wert; Kleidung, Musik und die Säle, in denen sie aufgeführt wird, sind fein aufeinander abgestimmt.

"Hol dir deinen beneFIT" : Einführung eines Gesundheitspasses zur Förderung der Studierendengesundheit an der Universität Paderborn - Köster, Carolin; Schaper, Niclas; Fergland, Dennis; Bischof, Sandra; Kussin, Ulrich; Kämpfe, Astrid (Bewegungsorientierte Gesundheitsförderung an Hochschulen)

Körperlich-sportliche Aktivität und subjektiver Gesundheitszustand sowie studiumsspezifisches Stressempfinden bei Studierenden - Kämpfe, Astrid; Köster, Carolin; Brandl-Bredenbeck, Hans-Pater (Bewegungsorientierte Gesundheitsförderung an Hochschulen)

Exploring Tradeoffs between Specialized Kernels and a Reusable Overlay in a Stereo-Matching Case Study - Kenter, Tobias; Schmitz, Henning; Plessl, Christian (International Journal of Reconfigurable Computing (IJRC))
FPGAs are known to permit huge gains in performance and efficiency for suitable applications but still require reduced design efforts and shorter development cycles for wider adoption. In this work, we compare the resulting performance of two design concepts that in different ways promise such increased productivity. As common starting point, we employ a kernel-centric design approach, where computational hotspots in an application are identified and individually accelerated on FPGA. By means of a complex stereo matching application, we evaluate two fundamentally different design philosophies and approaches for implementing the required kernels on FPGAs. In the first implementation approach, we designed individually specialized data flow kernels in a spatial programming language for a Maxeler FPGA platform; in the alternative design approach, we target a vector coprocessor with large vector lengths, which is implemented as a form of programmable overlay on the application FPGAs of a Convey HC-1. We assess both approaches in terms of overall system performance, raw kernel performance, and performance relative to invested resources. After compensating for the effects of the underlying hardware platforms, the specialized dataflow kernels on the Maxeler platform are around 3x faster than kernels executing on the Convey vector coprocessor. In our concrete scenario, due to trade-offs between reconfiguration overheads and exposed parallelism, the advantage of specialized dataflow kernels is reduced to around 2.5x.

Easy-to-Use On-The-Fly Binary Program Acceleration on Many-Cores - Damschen, Marvin; Plessl, Christian (Proceedings of the 5th International Workshop on Adaptive Self-tuning Computing Systems (ADAPT))
This paper introduces Binary Acceleration At Runtime(BAAR), an easy-to-use on-the-fly binary acceleration mechanismwhich aims to tackle the problem of enabling existentsoftware to automatically utilize accelerators at runtime. BAARis based on the LLVM Compiler Infrastructure and has aclient-server architecture. The client runs the program to beaccelerated in an environment which allows program analysisand profiling. Program parts which are identified as suitable forthe available accelerator are exported and sent to the server.The server optimizes these program parts for the acceleratorand provides RPC execution for the client. The client transformsits program to utilize accelerated execution on the server foroffloaded program parts. We evaluate our work with a proofof-concept implementation of BAAR that uses an Intel XeonPhi 5110P as the acceleration target and performs automaticoffloading, parallelization and vectorization of suitable programparts. The practicality of BAAR for real-world examples is shownbased on a study of stencil codes. Our results show a speedup ofup to 4 without any developer-provided hints and 5.77 withhints over the same code compiled with the Intel Compiler atoptimization level O2 and running on an Intel Xeon E5-2670machine. Based on our insights gained during implementationand evaluation we outline future directions of research, e.g.,offloading more fine-granular program parts than functions, amore sophisticated communication mechanism or introducing onstack-replacement.

Improving Packet Processing Performance in the ATLAS FELIX Project – Analysis and Optimization of a Memory-Bounded Algorithm - Schumacher, Jörn; T. Anderson, J.; Borga, A.; Boterenbrood, H.; Chen, H.; Chen, K.; Drake, G.; Francis, D.; Gorini, B.; Lanni, F.; Lehmann-Miotto, Giovanna; Levinson, L.; et al. (Proc. Int. Conf. on Distributed Event-Based Systems (DEBS))

Aktuelles Schlagwort: Approximate Computing - Plessl, Christian; Platzner, Marco; Schreier, Peter J. (Informatik Spektrum)
Keywords: approximate computing; survey

Transparent offloading of computational hotspots from binary code to Xeon Phi - Damschen, Marvin; Riebler, Heinrich; Vaz, Gavin Francis; Plessl, Christian (Proceedings of the 2015 Conference on Design, Automation and Test in Europe (DATE))
In this paper, we study how binary applications can be transparently accelerated with novel heterogeneous computing resources without requiring any manual porting or developer-provided hints. Our work is based on Binary Acceleration At Runtime (BAAR), our previously introduced binary acceleration mechanism that uses the LLVM Compiler Infrastructure. BAAR is designed as a client-server architecture. The client runs the program to be accelerated in an environment, which allows program analysis and profiling and identifies and extracts suitable program parts to be offloaded. The server compiles and optimizes these offloaded program parts for the accelerator and offers access to these functions to the client with a remote procedure call (RPC) interface. Our previous work proved the feasibility of our approach, but also showed that communication time and overheads limit the granularity of functions that can be meaningfully offloaded. In this work, we motivate the importance of a lightweight, high-performance communication between server and client and present a communication mechanism based on the Message Passing Interface (MPI). We evaluate our approach by using an Intel Xeon Phi 5110P as the acceleration target and show that the communication overhead can be reduced from 40% to 10%, thus enabling even small hotspots to benefit from offloading to an accelerator.

FELIX: a High-Throughput Network Approach for Interfacing to Front End Electronics for ATLAS Upgrades - Anderson, J; Borga, A; Boterenbrood, H; Chen, H; Chen, K; Drake, G; Francis, D; Gorini, B; Lanni, F; Lehmann Miotto, G; Levinson, L; Narevicius, J; et al. (Journal of Physics: Conference Series)
The ATLAS experiment at CERN is planning full deployment of a new unified optical link technology for connecting detector front end electronics on the timescale of the LHC Run 4 (2025). It is estimated that roughly 8000 GBT (GigaBit Transceiver) links, with transfer rates up to 10.24 Gbps, will replace existing links used for readout, detector control and distribution of timing and trigger information. A new class of devices will be needed to interface many GBT links to the rest of the trigger, data-acquisition and detector control systems. In this paper FELIX (Front End LInk eXchange) is presented, a PC-based device to route data from and to multiple GBT links via a high-performance general purpose network capable of a total throughput up to O(20 Tbps). FELIX implies architectural changes to the ATLAS data acquisition system, such as the use of industry standard COTS components early in the DAQ chain. Additionally the design and implementation of a FELIX demonstration platform is presented and hardware and software aspects will be discussed.

Einleitung: Organisationen und Konventionen - Knoll, Lisa (Organisationen und Konventionen)

Organisationen und Konventionen. Die Soziologie der Konventionen in der Organisationsforschung

The Hidden Regulation of Carbon Markets - Knoll, Lisa (Historical Social Research)

MiLeNa – ein überregionales Programm zur MINT-Lehrernachwuchsförderung - Salinga, Christian; Heinke, Heidrun; Jonas-Ahrend, Gabriela; Theyßen, Heike; Bahr, Ursula; Erb, Roger